TINDAK TUTUR DALAM TRADISI PERNIKAHAN MASYARAKAT MADURA PADA ERA MILLENIAL: KAJIAN SOSIOPRAGMATIK - Kusumawati, Hesty; Innayah, Innayah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia)
Humans are social creatures who have the nature to live together, side by side, and they need one to each other to achieve physically and mentally peace in order to share the joys and sorrows of living life, therefore they create a marriage. Marriage is a sacred event that binds man and woman, involving two families, both man and woman. In the use of language it is believed that the meaning is very closely related to the form. However, each language has its own characteristics and uniquenessess. Likewise, the Madurese language has special characteristics and uniquenessess. One of the uniqueness is manifested in the form of Madurese marriage tradition. The tradition of Madurese marriages has several stages, the first stage is namely engagement (abhÃ¢kalan), the second stage is marriage, and the last namely is post-marriage. In this study, researcher used a qualitative descriptive approach with the method of listening. This study aims to see how the speech acts that appears in the speech of the Madurese in the Madurese marriage tradition in the millennial era.